Protein with negative surface charge distribution, Bnr1, shows characteristics of a DNA‐mimic protein and may be involved in the adaptation of Burkholderia cenocepacia. Issue 1 (6th February 2022) - Dennehy, Ruth; Duggan, Niamh; Dignam, Simon; McCormack, Sarah; Dillon, Eugene; Molony, Jessica; Romano, Maria; Hou, Yueran; Ardill, Laura; Whelan, Matthew V. X.; Drulis‐Kawa, Zuzanna; Ó'Cróinín, Tadhg; et al.
Abstract: Adaptation of opportunistic pathogens to their host environment requires reprogramming of a vast array of genes to facilitate survival in the host. Burkholderia cenocepacia, a Gram‐negative bacterium with a large genome of ∼8 Mb that colonizes environmental niches, is exquisitely adaptable to the hypoxic environment of the cystic fibrosis lung and survives in macrophages. We previously identified an immunoreactive acidic protein encoded on replicon 3, BCAS0292. Deletion of the BCAS0292 gene significantly altered the abundance of 979 proteins by 1.5‐fold or more; 19 proteins became undetectable while 545 proteins showed ≥1.5‐fold reduced abundance, suggesting the BCAS0292 protein is a global regulator. Moreover, the ∆BCAS0292 mutant showed a range of pleiotropic effects: virulence and host‐cell attachment were reduced, antibiotic susceptibility was altered, and biofilm formation enhanced. Its growth and survival were impaired in 6% oxygen. In silico prediction of its three‐dimensional structure revealed BCAS0292 presents a dimeric β‐structure with a negative surface charge. The ΔBCAS0292 mutant displayed altered DNA supercoiling, implicated in global regulation of gene expression. Three proteins were identified in pull‐downs with FLAG‐tagged BCAS0292, including the Histone H1‐like protein, HctB, which is recognized as a global transcriptional regulator. We propose that BCAS0292 protein, which we have named B urkholderia n egatively surface‐charged r egulatory protein 1 (Bnr1), acts as a DNA‐mimic and binds to DNA‐binding proteins, altering DNA topology and regulating the expression of multiple genes, thereby enabling the adaptation of B. cenocepacia to highly diverse environments. Abstract : B urkholderia n egatively surface‐charged r egulatory protein 1 (Bnr1) is an acidic protein expressed by Burkholderia cenocepacia that is upregulated in the stationary phase; in response to low oxygen stress; or the hypoxic environment of the chronically infected cystic fibrosis lung. It possesses a negatively charged surface and its deletion dramatically alters the abundance of over a thousand proteins in the cell, with multiple effects on pathogenesis. We show that Bnr1 binds to histone‐like binding proteins and behaves as a DNA‐mimic protein.